A Study of Support Systems for Women in Medicine: Dual Roles of Professional and Mother - NIWA, Haruo; IWAI, Kuni; UEHARA, Ritei; KURASAWA, Miwa; OJIMA, Toshiyuki; TAKAYASHIKI, Ayumi; NIWA, Miwako; KAJII, Eiji; OKI, Izumi (Igaku Kyoiku / Medical Education (Japan), 2003)
We examined issues in balancing professional obligations with family needs, especially parenting, in female physicians. Questionnaires were given to all female physicians who had graduated from Jichi Medical School. Of the 196 graduates, 155 responded (79.1%), and younger graduates accounted for a greater proportion of subjects. Although many female physicians did not live with their parents, female physicians or their parents were usually responsible for caring for children when they become ill. Many respondents demanded better access to day care and greater flexibility in accepting sick children. Female physicians should contribute to society using the knowledge and skills they acquired in medical school; to do so they need support systems in their workplace and child-care services.